Sustainable development of the enantonym meanings under the influence of the context (on the German language material) - Ostrikova Galina (E3S Web of Conferences, 2023)
The article explores the concept of enantiosemy as a semantic category of language. Along with other categories of language, enantiosemy exists at all language levels: morphemic, grammatical, lexical, phraseological and syntactic. The article deals with enantiosemy units at the lexical, phraseosyntactic and syntactic levels of the German language. For the actualization of enantonyms, the context plays a decisive role. The meaning of enantiosemy lexical units is realized in the so-called “mixed” context, when several actualizers determine the meaning of units. At the phraseosyntactic level, syntactic phraseological units capable of expressing enantiosemy meanings, namely communicames, are considered. Interrogative sentences with enantiosemy rethinking are presented at the syntactic level. As a result of such rethinking, they receive the secondary meaning opposite to the direct one: more often negative and less often positive. The linguistic and extralinguistic context contributes to this. The last type of context is predominant in determining the meaning of enantonyms of different levels in the German language. The sustainable development of opposite meanings of enantonyms under the influence of context at all levels of the language is traced.